IMPLICATIONS OF PERSONAL DATA LEAKS FROM THE PUBLICATION OF JUDICIAL DECISIONS IN THE SUPREME COURT DECISION DIRECTORY ON PERSONAL DATA PROTECTION - Roni Evi Dongoran; Nurini Aprilianda; Faizin Sulistio (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The publication of court decisions in the Indonesian Supreme Court Decision Directory is a form of public information disclosure. However, in practice, these publications often contain the personal data of the parties involved, such as their National Identification Number, full address, and the identity of victims, even in cases where this information should be redacted. This situation creates the potential for personal data leaks that could open up opportunities for information misuse, violate privacy rights, and pose security risks. This study aims to analyze the implications of personal data leaks originating from the publication of court rulings in the Supreme Court's ruling directory on personal data protection in the era following the enactment of Law-Law Number 27 of 2022 concerning Personal Data Protection and the issuance of the Supreme Court Chief Justice's Decree Number 2-144/KMA/SK/VIII/2022 concerning Public Information Service Standards in Courts. The research method used is normative juridical with a legislative, case analysis, and conceptual approach, supplemented by a study of examples of publicly published decisions. The results of the study show that there are still discrepancies between the practice of publishing decisions and the obligation to protect personal data. These findings indicate the need to strengthen editorial policies, obscuring standards, and internal monitoring mechanisms so that the openness of judicial information does not sacrifice the privacy rights of the public. This study is expected to contribute to improving the governance of decision publication and strengthening the personal data protection regime in Indonesia.